Eucalyptus in Malaysia: review on environmental impacts - Zaiton, Samdin; Mohd Razali, Sheriza; Rosman, Nur Aini Shifaa; Khaw, Alfred; Kamaruddin, Norfaryanti (De Gruyter, 2020)
Development of forest plantation is mainly intended to provide income opportunity and to ensure the improvement of the socioeconomics of society. Sabah Softwood Berhad (SSB) is one of the private companies that pioneered the development and commercialization of fast growing timber species and forest plantation. The Eucalyptus plantation in SSB was initiated in response to the emergence of fungal disease that implicated the environment. Nevertheless, the impacts of plantation to the environment regarding water use, soil erosion, nutrient loss, pest and disease, biodiversity, soil quality and hydrology are reviewed. The disputes among various scientists over the physiological and plantation aspects of Eucalyptus, especially their implication towards the environment are also discussed. This paper aims to present information on the impacts posed by the Eucalyptus plantation that will guide the planters and policy makers in facilitating a management plan to mitigate the impacts of this species to the environment.